STUDENTS' HEALTHY LIFESTYLE IN THE EDUCATIONAL SYSTEM: HOW NOT TO MISS THE POINT? - Elena P. Demkina (Moscow Polytechnic University, 2016)
The article presents some results of the author's research, which combines elements of two research strategies: the desk analysis (literature and sources) and field (a poll of students of the Tatarstan Republic). The study aims at analyzing the current forms and methods to formation of students' healthy lifestyle in the framework ofthe vocational training system. The analysis revealed that in spite of the represented in the literature an abundance of techniques to spread among the students knowledge on the theory of a healthy lifestyle and increase motivation for maintaining a healthy lifestyle, there is a lack of attention to such important aspect as the development of students' self-organization skills needed for successful formation of HLS.